Essentials of mathematics : - Hale, Margie (Mathematical Association of America, 2003)
Essentials of Mathematics is designed as both a textbook and outside reading for college students who want to prepare themselves for mathematics courses beyond the first-year level. The mathematical content includes logic, set theory and a theoretical development of the number systems, giving students practice at proving mathematical statements. There are no answers in the book, but a separate manual provides instructor support. The book makes an excellent reference for students beginning to take courses in which proofs play a major role. In addition to the course material, there are narratives on the nature of mathematics and the mathematics profession. These sections can be read without help or guidance.